Employment and the conduct of monetary policy in the euro area (European Central Bank (ECB), 2021)
This report discusses the role of the European Union's full employment objective in the conduct of the ECB's monetary policy. It first reviews a range of indicators of full employment, highlights the heterogeneity of labour market outcomes within different groups in the population and across countries, and documents the flatness of the Phillips curve in the euro area. In this context, it is stressed that labour market structures and trend labour market outcomes are primarily determined by national economic policies. The report then recalls that, in many circumstances, inflation and employment move together and pursuing price stability is conducive to supporting employment. However, in response to economic shocks that give rise to a temporary trade-off between employment and inflation stabilisation, the ECB's medium-term orientation in pursuing price stability is shown to provide flexibility to contribute to the achievement of the EU's full employment objective. Regarding the conduct of monetary policy in a low interest rate environment, model-based simulations suggest that history-dependent policy approaches - which have been proposed to overcome lasting shortfalls of inflation due to the effective lower bound on nominal interest rates by a more persistent policy response to disinflationary shocks - can help to bring employment closer to full employment, even though their effectiveness depends on the strength of the postulated expectations channels. Finally, the importance of employment income and wealth inequality in the transmission of monetary policy strengthens the case for more persistent or forceful easing policies (in pursuit of price stability) when interest rates are constrained by their lower bound.
Keywords: E24; E52; 330; Employment; monetary policy; heterogeneity